Consumption at long sight - Schulze, Gerhard (Marketing & Menedzsment, 2017)
THE AIMS OF THE PAPER Consumption is a changing social phenomenon that has its roots in history and looks set to undergo fundamental transformation in the future. Science has to assess consumption in a multidisciplinary way, not only in terms of the economic sciences, but also in terms of sociology, anthropology, psychology, philosophy, and ecology. These aspects are interrelated both in history and consumer biographies. The article starts with a look back on the history of consumption (including the author's childhood in post-war Germany) and ends with a view on its future. The purposes are (I) to identify specific stable features of consumption in the long range, (II) to describe the actual global situation as a mix of three stages of transition, and (III) to describe various facets of absurdity that may announce the coming of a post consumption era. The last section (IV) anticipates what could happen as a result of collective learning, of changing collective selfobservation and of normalization of new forms of creation of values. METHODOLOGY Methodologically the analysis is guided by the approach of Understanding Sociology according to Max Weber in combination with an anthropological interpretation of actors under the condition of continuous expansion of options since late 1811 century. MOST IMPORTANT RESULTS The results consist firstly in the specification of several universal features of consumption, secondly in the identification of the idea of arrival as opposed to the idea of increase as a contemporary global trend, thirdly in describing exemplarily four patterns of absurdity as stimuli of collective learning in the long range. RECOMMENDATIONS The recommendations concentrate on ways of new thinking and collective self-observation: normalization, distance, maturation, objectification, individualization, de-materialization, collective goods, and selfperception.